À l’affirmation « Tous pareils », l’Inventaire répond : « Et pourtant si différents ! » - Karine Girard (In Situ)
At first glance, this is a charmless “lycée” (France’s high school), like you see in many communes of France: a low-rise built to receive the children of the baby boom. But the school complex of Le Quesnoy (Nord department) is full of surprises. The construction, entrusted to Pierre Vivien, the already well-known Chief architect of the “bâtiments civils et palais nationaux”, the Civil buildings and National Palaces, was part of a collective purchase order of four ‘lycées’ made by the State, which was still a rare occurrence in those days. The study of the archives and buildings highlights a complex architectural programme, conducted by the same architect in two distinct phases (1959 and 1967). Even though the materials used were the same, the forms produced were different. Thus, while integrating the Ministry’s educational and architectural directives that often gave the “lycées” of the post-war period a similar appearance, the schools could be very unique in terms of building techniques implemented and materials used.Apart from the call into question of the uniformity of the “lycées” that were built during the post-war period, the work of the Inventory became the only architectural and photographic memory of this educational institution. The day school built by Vivien, was indeed destroyed in 2016. The archives found by the researcher from the architect’s office that was monitoring the maintenance of the day school were deposited at the very last moment in the "archives départementales”, the Departmental Archives (AD) of the Nord, as they were about to be destroyed at the same time as the building. Finally, this study has raised awareness of the value of the artwork created thanks to the 1% for art, which should enable its reinstallation under the right conditions of preservation and its promotion.